Is It Simply Gender? Content, Format, and Time in Political Knowledge Measures. Issue 2 (27th March 2018) - Ferrin, Monica; Fraile, Marta; García-Albacete, Gema
Abstract : Theories of democracy commonly assume that citizens must have a certain degree of information and factual knowledge to be able to understand the functioning of institutions, the performance of the incumbent government, and the actions of the main political actors. Political knowledge helps people to better assess their interest as individuals and as members of groups (Delli Carpini and Keeter 1996). Moreover, governments have more incentives to be responsive when they can be held accountable, but citizens are able to hold governments accountable for their actions only when they know what governments are actually doing.